The identity of Ranunculus ailaoshanicus (Ranunculaceae) from China - Yuan, Qiong; Yang, Qin-Er (Phytotaxa, 2017)
We demonstrate that Ranunculus ailaoshanicus (Ranunculaceae) described from Ailao Shan, Yunnan, China, is conspecific with R. ficariifolius, a very widespread and highly variable species. We therefore place the former in synonymy within the latter.